Centre for Foundation Studies Sejahtera - Shaharudin, Mir Azrul (IIUM Press, 2021)
Centre for Foundation Studies (CFS) Sejahtera is part of IIUM's Sustainable Development Goals (SDG) project which started in late 2019. The project comprise of six (6) main initiatives which support eight (8) SDGs.